Signal on the Margin: Behavior of Levered Investors and Future Economic Conditions - Deuskar, Prachi; Kumar, Nitin; Poland, Jeramia Allan (Review of Finance, 2020)
Abstract Margin capacity, defined as the aggregate excess debt capacity of investors buying securities on margin, strongly predicts (i) lower S&P 500 returns, (ii) lower growth in aggregate earnings, dividends, employment, and overall economic activity, (iii) higher macro, financial, and policy uncertainty, (iv) lower interest rates, (v) tighter lending standards by banks, and (vi) lower intermediary equity capital. High margin capacity is a precursor, not a response, to borrowing and intermediary constraints and higher volatility. It typically arises when levered investors with profitable past positions limit their leverage. We interpret that it reflects informed investors’ conservatism ahead of bad times.